The influence of brand positioning brand image and price perception on repurchase intention toward finally found you skincare products in Batam city - Salma Saqilah Lubis; Alice Erni Husein (International Journal of Applied Finance and Business Studies, 2026)
This study examined the influence of brand positioning, brand image, and price perception on consumers’ repurchase intention toward Finally Found You skincare products in Batam City. The research applied a quantitative approach using a survey method with purposive sampling techniques involving 100 respondents who had previously used the product. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS 29. The findings demonstrated that brand positioning, brand image, and price perception each had a positive and statistically significant effect on repurchase intention, both partially and simultaneously. Brand positioning strengthened consumer recognition and confidence toward the product, while brand image enhanced trust and emotional attachment to the brand. Price perception also contributed significantly, indicating that consumers perceived the products as competitively priced and aligned with the quality and benefits received. Simultaneous testing confirmed that the three independent variables collectively explained a substantial proportion of the variation in repurchase intention. The study highlights the importance of strategic brand management and pricing policies in strengthening customer loyalty and sustaining competitiveness within the Indonesian skincare industry.